2020
DOI: 10.1007/s00330-020-07225-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low-dose chest CT imaging of COVID-19 patients using a deep residual neural network

Abstract: Objectives The current study aimed to design an ultra-low-dose CT examination protocol using a deep learning approach suitable for clinical diagnosis of COVID-19 patients. Methods In this study, 800, 170, and 171 pairs of ultra-low-dose and full-dose CT images were used as input/output as training, test, and external validation set, respectively, to implement the full-dose prediction technique. A residual convolutional neural network was applied to generate full-dose fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 31 publications
1
66
0
1
Order By: Relevance
“…A number of studies applied deep or machine learning algorithms for COVID-19 outbreak prediction, detection/segmentation of infected pneumonia regions from radiologic images, as well as new drug development and disease screening [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. In diagnostic studies, artificial intelligence approaches have been applied to various medical imaging modalities, including radiography, ultrasound, and CT to build more accurate detection/diagnostic models [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies applied deep or machine learning algorithms for COVID-19 outbreak prediction, detection/segmentation of infected pneumonia regions from radiologic images, as well as new drug development and disease screening [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. In diagnostic studies, artificial intelligence approaches have been applied to various medical imaging modalities, including radiography, ultrasound, and CT to build more accurate detection/diagnostic models [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 in [29]). Recently, many efforts have been devoted to these problems [40][41][42][43]. And in this study, to address the first and second issues listed above, we designed a 3D deep learning model that uses the simple binary labels to identify mild COVID-19 pneumonia and greatly reduces the manual intervention.…”
Section: Discussionmentioning
confidence: 99%
“…CT was shown to be useful for follow-up evaluations and for prognosis (14,15). Although low-dose CT was recommended as the standard scanning protocol to minimize the radiation dose, studies showed that ultra-low-dose CT would make it more difficult to detect subtle GGOs (16). Full radiation dose scanning was therefore established as the technological society consensus (17).…”
Section: N P R E S Smentioning
confidence: 99%